The globalisation of migration: has the world really become more migratory? - Czaika, M; de Haas, H (International Migration Institute, 2013)
Although it is commonly believed that the volume, diversity, geographical scope and overall complexity of international migration have increased as part of globalisation processes, this idea has remained largely untested. This paper aims to fill this gap by mapping shifts in global migration patterns between 1960 and 2000. In order to simultaneously capture changes in the spread, distance and intensity of migration, this paper elaborates indices for emigration dispersion, immigration diversification and migration globalisation. The results challenge the idea that there has been a global increase in volume, diversity and geographical scope of migration. While international migration has not accelerated in relative terms, main migratory shifts have been directional and are linked to major geopolitical and economic transformations, such as the rise of new 'migration magnets’, development-driven emigration hikes and the lifting of emigration restrictions. Migration has globalized from a destination country perspective but hardly from an origin country perspective, with migrants from an increasingly diverse array of non-European origin countries concentrating in a shrinking pool of prime destination countries. The global migration map has thus become more skewed. Rather than refuting the globalisation of migration hypothesis, this seems to reflect the asymmetric nature of globalisation processes in general.